PELATIHAN BAHASA INGGRIS UNTUK ANAK DI TPA DUSUN MOJOSARI SITIMULYO PIYUNGAN BANTUL - surip Haryani; Lina Asiyah (ABDIMAS Madani, 2019)
In pre-school education, some PAUD and TPA have already introduced English even though there are only a few introductions but some have not provided English language material at all. English language training for TPA students is important to do to prepare children to learn English lessons they will get in elementary school and it can be given as knowledge for children. In Dusun Mojosari, English language has not become one of the regular learning menus due to the limited human resources of existing teachers. STIKes Madani Yogyakarta in its efforts to realize the mission of being a college in an effort to provide real contribution to the benefit of the people, is trying to provide training and service to the community especially around institutions. The institution not only provides health training but also training related to foreign languages given by lecturers of English. One of the training was also given for TPA students in Dusun Mojosari Situmulyo Piyungan Bantul. The purpose of this training is to provide basic training for TPA students in Dusun Mojosari to help them to have the basic reading skills in English from a very basic level. This material is necessary to be given considering the age of students in the TPA in Mojosari which they are mostly in pre-primary age. Students were given the correct English pronunciation material and given the opportunity to practice pronunciation (pronunciation) that is appropriate from the alphabet level then to the English phrase or word given. It is expected that the training could give knowledge and experience as provision for them to get English lessons while entering the elementary school so that they can be more easy in learning English.